IMPACT OF NARROWBAND UVB THERAPY ON HISTOPATHOLOGICAL CHANGES IN VITILIGO: A RANDOMIZED CONTROLLED TRIAL - Dr. Muhammad Umar Ali Khan; Dr. Muhammad Nasir Khan; Dr. Fatima Rashid; Dr. Mehwish Niazi; Dr. Zertaj Kashif; Dr. Muhammad Bilal Pasha; Dr. Farah Naz Tahir (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Narrowband ultraviolet B (NB-UVB) phototherapy has emerged as a cornerstone in vitiligo management; however, its precise histopathological impact remains inadequately characterized. This randomized controlled trial aimed to evaluate the histopathological alterations induced by NB-UVB therapy in vitiligo patients. Forty individuals with non-segmental vitiligo were randomized into two groups: Group A received NB-UVB therapy thrice weekly for 12 weeks, while Group B served as controls without phototherapy. Pre- and post-treatment skin biopsies were analyzed for melanocyte count, epidermal thickness, and inflammatory infiltrates. Results demonstrated a significant increase in melanocyte density (mean increase: 3.2 ± 0.5 cells/mm²; p